REKAYASA GENETIK DALAM PERSPEKTIF ETIKA KRISTEN: TELAAH TEOLOGIS ATAS MARTABAT MANUSIA SEBAGAI IMAGO DEI - Elizama Gulo; Hans Prawira Anggara Taliak; Alberta Ella Saryani Zai; Margareth Inggrid Rajaguguk (Jurnal Padamu Negeri, 2026)
This study examines the ethical boundaries of genetic engineering from a Christian theological perspective, specifically through the lens of the Imago Dei doctrine. Using a qualitative library research approach, this research analyzes the theological and ethical implications of CRISPR-Cas9 technology and genetic enhancement practices. The findings reveal three critical tensions: (1) the distinction between therapeutic intervention and genetic enhancement, (2) the boundaries of divine sovereignty versus human stewardship responsibility, and (3) the commodification risk of human life through genetic modification. This study concludes that while somatic gene therapy can be ethically justified as part of healing ministry, germline editing and enhancement technologies pose fundamental challenges to human dignity as bearers of God’s image. The research recommends that Christian ethics should guide technological development by prioritizing the intrinsic value of human life over utilitarian genetic quality standards.